Performance analysis of the ionic liquid [EMIM][DEP] in absorption refrigeration systems - Kai-Shing Yang; Jia-Wei Zheng; Shi-Feng Zhuang; Shih-Kuo Wu; Chih-Hao Chen; Kai-Hsiang Lin (Results in Engineering)
This study investigates the performance of the absorption refrigeration systems using [EMIM][DEP]-based ([EMIM][DEP]/H2O, [EMIM][DEP]/C2H5OH, [EMIM][DEP]/CH3OH) and conventional solutions (LiBr/H₂O, LiCl/H₂O, H2O/NH3) subject to varying operating conditions. The analysis is carried out through numerical simulations, employing the thermodynamic model specifically developed to represent the absorption cycle. While conventional absorbent/refrigerant pairs such as LiBr/H₂O and LiCl/H₂O yield the highest coefficients of performance (COP), [EMIM][DEP]-based solutions show considerable promise as potential replacements. In particular, [EMIM][DEP]/H2O and [EMIM][DEP]/C2H5OH solutions showed remarkable performance, revealing COPs within a comparable range. Besides, the [EMIM][DEP]/CH3OH solution demonstrates superior performance at generator temperatures exceeding 100 °C, suggesting its suitability for higher temperature applications. The overall COP of the absorption system using [EMIM][DEP]/CH3OH as the absorbent is found to be 1.4 % to 2.9 % higher compared to that of the systems using [EMIM][DEP]/H2O and [EMIM][DEP]/C2H5OH. As the temperature rises close to 130 °C, the performance of the system with [EMIM][DEP]/CH3OH solution becomes increasingly comparable to that of the LiBr/H2O system, thereby positioning [EMIM][DEP] as a viable and effective alternative to be implemented in the absorption systems. The results indicate that, despite a modest COP performance, [EMIM][DEP]-based pairs offer significant advantages over conventional working fluids (e.g. LiBr/H₂O and LiCl/H₂O), including intrinsic immunity to crystallization and favorable thermal stability across a broad temperature range (∼80 °C to 200 °C). In a whole, this study demonstrates the immense potential of using [EMIM][DEP]-based solutions in the development of an effective and sustainable absorption technology, particularly in scenarios where the system demands high operational temperatures.